The Management Of National Parks In Algeria: Overview, Means And Constraints. Case Of National Parks In The North. - Kerbiche, Fatima; Akninesouidi, Rosa (جامعة الوادي - University of Eloued, 2023)
The objective of this article is to establish an overview of the management of Algerian national parks (ANP), in terms of human and financial resources, which reflects both their functioning and the commitment of the State in favor of the protection and enhancement of the natural heritage. In this context, we have formulated the following main questions: How is the management of NAPs implemented in terms of human and financial resources? What are the constraints encountered? To do this, we will opt for a study of eight national parks in northern Algeria; these are EL-Kala, Chréa, Djurdjura, Theniet-El-Had, Belezma, Gouraya, Taza and Tlemcen, based on an analytical and descriptive study.
مقال
Keywords: Natiional Parks ; Human resources ; Financial resources ; Natural heritage ; Constraints